19.4 RELATIONAL MEMORY AND HIPPOCAMPAL FUNCTION IN EARLY AND CHRONIC SCHIZOPHRENIA. (9th April 2019) - Avery, Suzanne; Rogers, Baxter; McHugo, Maureen; Armstrong, Stephanie; Woodward, Neil; Blackford, Jennifer; Heckers, Stephan
Abstract: Background: Humans integrate information into cohesive relational memories in order to choose relevant behaviors and update prior expectations. The flexible use of relational memory to guide current behavior depends on the hippocampus and its network. Schizophrenia is associated with substantial deficits in relational memory as well as hippocampal dysfunction. As relational memory deficits are a significant predictor of functional outcome, relational memory may be a useful prognostic marker in the early stage of illness. While there is evidence for progressive structural changes of the hippocampus in schizophrenia, it is unclear whether relational memory impairments and hippocampal function also decline. Here, we investigate relational memory and hippocampal function in cohorts of early and chronic schizophrenia patients. Methods: Relational memory was studied by tracking eye movements during retrieval of face-scene associations. In an fMRI study, participants were exposed to repeated face and object images to study novelty response and habituation in the anterior and posterior hippocampus. Habituation was examined at a short timescale, to study sensory filtering based on prior experience and expectation, and at a longer timescale, to study a circuit-level integration of information into existing memories. Results: Both early and chronic schizophrenia patients showed deficits in relational memory ability, although deficits were subtler in the early stage of illness. Early psychosis patients showed smaller novelty responses and less habituation to stimulus properties in the anterior hippocampus. In comparison, chronic schizophrenia patients showed anterior hippocampal habituation deficits across the task, suggesting a disrupted integration of information into memory. Conclusions: These studies provide evidence that both relational memory and hippocampal function are deficient in the early stage of psychosis and suggest deficits progress with illness, although longitudinal studies are necessary. These findings further our understanding of the pathophysiology of relational memory in schizophrenia and suggest a possible model for illness progression.